Implications of Digital Policing with the Application of Artificial Intelligence in Positive Law in Indonesia - Utama, Robertus Wardhana; Lamijan, Lamijan; Susilowati, Tri (Pusat Publikasi Nusantara, 2024)
Artificial Intelligence (AI) has become a useful tool for the police in curbing traffic violations and improving road safety. This research aims to examine how AI is applied to positive law in Indonesia. By focusing on positive law, the study provides a focused analysis of AI's impact on existing legal statutes and regulations in Indonesia, potentially examining case studies, legal precedents, or specific AI tools used within the Indonesian legal framework. This geographical and jurisdictional focus offers unique insights into the challenges and opportunities presented by AI within the legal framework, facilitating comparisons with AI in other countries or regions. The findings offer valuable information for policymakers, legal practitioners, and technologists on effectively integrating AI into the legal system. This article specifies that electronic equipment may be utilized to facilitate the prosecution of infractions in the realm of traffic and road transportation, and the resultant data obtained through this equipment can serve as admissible evidence in legal proceedings.